Financial technology as a driver of poverty alleviation in China: Evidence from an innovative regression approach - Yafen Ye; Shenglan Chen; Chunna Li (Journal of Innovation & Knowledge (JIK), 2022)
Despite the booming development of financial technology (fintech) in China, little academic literature has explored the effects of fintech on poverty. This paper explores the effects of fintech on poverty alleviation in the provinces of China. The sample includes data for 31 provinces for the period of 2011 to 2020. To reflect the technological innovation of finance, we first use web crawler technology and word frequency analysis to collect variables, and then construct a fintech index for each province. Due to the heterogeneity in poverty among various provincial regions, we further propose a novel sparse support vector quantile regression to examine the effectiveness of fintech on poverty reduction within individual Chinese provinces. Quantile estimators of the proposed method are used as empirical "location" measures for poverty. The empirical results show that although the development of fintech index is uneven among provincial regions, fintech effectively reduces poverty in every province. Moreover, the positive effects of fintech on poverty alleviation are much stronger in low-income provinces than in high-income provinces. Therefore, policy-makers and practitioners should build more digital financial technology systems, especially in Chinese low-income provinces.
Keywords: C6; G2; R1; 650; Fintech; Poverty alleviation; Quantile regression; Support vector regression